COMPUTER TRAINING TO IMPROVE HUMAN RESOURCES OF GKI PNIEL KOTARAJA CONGREGATION: PELATIHAN KOMPUTER UNTUK MENINGKATKAN SDM JEMAAT GKI PNIEL KOTARAJA - Reni Koibur; Axelon S Renyaan; Fegie Y Wattimena; Ermi D Sumanik; Clara E Anakota; Brianth T Fester (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The need of knowledge and mastery of Information technology is needed to improve the quality of Human Resources along with the increasingly rapid advances in information technology. The lack of skills in operating ICT, in this case, Ms.Office and Google facilities among GKI Pniel Kotaraja Youth and Women, has encouraged the education sector. The implementation method used is analysis, preparation, and implementation. This computer training activity was carried out for three days. At the beginning of the activity, a pretest was distributed to measure participants' understanding of operating Ms. Office and Google. Monitoring and evaluation are carried out by giving pre-tests and post-tests to measure the extent to which participants understand and master the material. The results of this training were that 72.77% had been able to improve their competency in operating Ms. Office and Google